2018
DOI: 10.1177/2050312118801709
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of five procedures for great saphenous vein reflux in a Norwegian healthcare setting or societal setting

Abstract: Objective:The aim of this work was to estimate cost-effectiveness of five common procedures for varicose vein surgery (high ligation and stripping, radiofrequency ablation, endovenous laser ablation, steam vein sclerosis and cyanoacrylate glue) in a Norwegian setting from both a societal and a healthcare payer perspective.Design:Cost-effectiveness analysis using decision tree modelling.Methods:A structured literature search was conducted to estimate the clinical effectiveness and the rate of complications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…Another recent review and economic modelling paper finds EVLA to be most cost-effective in Norway from a societal (patient and NHS cost) perspective, and steam vein sclerosis to be most cost-effective from a NHS-only perspective over a one-year time horizon [72].…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Another recent review and economic modelling paper finds EVLA to be most cost-effective in Norway from a societal (patient and NHS cost) perspective, and steam vein sclerosis to be most cost-effective from a NHS-only perspective over a one-year time horizon [72].…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…[10] Bozkurt et al [11] reported that the one-year success rate of endovenous thermal ablation with laser and glue ablation was 92.2% and 95.8%, respectively (P=0.138) in patients without warfarin therapy. In addition, Park [5] reported that the VenaSeal system was found to be safe and efficient for the treatment of reflux of small saphenous vein with 100% patient's satisfaction. The main advantages of glue ablation over endovenous thermal ablation are including less pain, hematoma, and ecchymosis.…”
Section: Endovenousmentioning
confidence: 99%
“…The main advantages of glue ablation over endovenous thermal ablation are including less pain, hematoma, and ecchymosis. [5] Due to potential postprocedural hemorrhage, the majority of authors are recommended to discontinue warfarin therapy prior to procedure. [9] However, some authors advocated that continuation of anticoagulant therapy does not affect the success rate of endovenous thermal ablation and foam sclerotherapy.…”
Section: Endovenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Det finnes eksempler på at forskjellige perspektiv kan føre til helt ulike konklusjoner om kostnadseffektiviteten. I en publikasjon fra 2018 gjennomførte vi en bred analyse av tilgjengelige behandlingsmodaliteter for åreknutekirurgi i det norske helsevesenet (4). Analysen viste at nye endovaskulaere teknikker (som damp eller laser) kom best ut, i saerdeleshet sammenholdt med tradisjonell kirurgi.…”
unclassified